Are you sure?5 *186x = 26
How did get that answer
Answer is x=-In(5) - In(26)/6(In(2)-2In3)
It looks like, in part, you have gotten you rules about logarithms mixed up:5 *186x = 26
How did get that answer
Answer is x=-In(5) - In(26)/6(In(2)-2In3)
\(\displaystyle 5(18^{6x})=26\\\log(5)+6x[2\log(3)+\log(2)]=\log(13)+\log(2)\\x=\dfrac{\log(13)+\log(2)-\log(5)}{6[2\log(3)+\log(2)]}\)5 *186x = 26
How did get that answer x=-In(5) - In(26)/6(In(2)-2In3)
I must be not seeing something as I agree with Denis' result.5 *186x = 26
Why not simply: x = LOG(26/5) / [6LOG(18)] ?
Like 2 * 6 = 12, not necessary to show 2 * 6 = 2 * 2 * 3 = 12
For the record it is Ln, not In. Ln stands for something like log natural.5 *186x = 26
How did get that answer
Answer is x=-In(5) - In(26)/6(In(2)-2In3)
Possible typo (or else I'm already too drunk).\(\displaystyle 5(18^{6x})=26\\\log(5)+6x[2\log(3)+\log(2)]=\log(13)+\log(2)\\x=\dfrac{\log(13)+\log(2)-\log(5)}{6[2\log(3)+\log(2)]}\)
DISCLAIMER: Beer soaked rambling/opinion/observation/reckoning ahead. Read at your own risk. Not to be taken seriously. In no event shall the wandering math knight-errant Sir jonah in his inebriated state be liable to anyone for special, collateral, incidental, or consequential damages in connection with or arising out of the use of his beer (and tequila) powered views.
Possible typo (or else I'm already too drunk).
This could have been
\(\displaystyle 5(18^{6x})=26\\\log(5)+6x[\log (2)+\log(3)+\log(3)]=\log(13)+\log(2)\\x=\dfrac{\log(13)+\log(2)-\log(5)}{6[\log(2)+\log(3)+\log(3)]}\)
Sorry about that Sir pka.\(\displaystyle {6[\log(2)+\log(3)+\log(3)]}={6[\log(2)+2\log(3)]}\)